Understanding the molecular conformations of Na-dimyristoylphosphatidylglycerol (DMPG) using DFT-based method - Mishra, Deepti; Pal, Sourav; Krishnamurty, Sailaja (Molecular Simulation, 2011)
The molecular conformations of phospholipids comprising a lipid bilayer determine the physico-chemical properties of the latter. In this study, we attempt to understand the various possible conformations available for an anionic lipid molecule dimyristoylphosphatidylglycerol (DMPG) with Na as its charge-compensating cation. The various possible molecular orientations available for lipid molecule are analysed using a density functional theory-based method. Our study reveals a rich conformational space with two different types of glycerol body orientations, more commonly known as rotamers. Interestingly, this is in agreement with the molecular conformations proposed earlier by NMR studies on lipid monomer solutions. We demonstrate that these conformations are an outcome of delicate balance of electrostatic and van der Waals forces along with intra-molecular hydrogen bonds achieved by a critical combination of torsion angles. Na(+) ions are seen to interact predominantly with the oxygen atoms of the glycerol groups in tail and head along with that of phosphate oxygen atoms leading to a cage-like orientation of lipid molecule around the Na(+). Following the conformational analysis, we attempt to evaluate the electronic properties of few low-lying conformations. This study shows that though the water molecules screen the Na-O(lipid) interactions, they do not dramatically modify the Na-O(lipid) bond distances. The lipid conformation retains the cage-like structure around the Na(+) in the presence of water molecules. Some amount of charge transfer from the water molecules to Na ion is noted. The water molecules modify the phosphate-tail glycerol group interactions leading to a more stable Na-DMPG-H(2)O and Na-DMPG-4H(2)O complexes.
Keywords: DFT; DMPG; molecular conformations; rotamer and hydration energy